Shift Kerja dan Beban Kerja dengan Tingkat Stres Tenaga Kesehatan Post Pandemi COVID-19 - Ketut Suka; Sulis Diana; Nurwidji Nurwidji; Dhonna Anggreni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the relationship between work shifts and workload with the level of work stress among Gerokgak Health Center health workers. The method used is quantitative analysis through a cross-sectional approach. The results showed that work shifts and work stress levels obtained values (p=0.000 and r=0.846), and workload and work stress levels obtained values (p=0.000 and r=0.777). In conclusion, work shifts and workload have a significant positive relationship and influence on work stress levels. Keywords: Workload, Work Shift, Work Stress Level